1986
DOI: 10.1007/bf01656105
|View full text |Cite
|
Sign up to set email alerts
|

Total gastrectomy: Is the early postoperative morbidity and mortality influenced by the choice of surgical procedure?

Abstract: From 1973 to 1982, seventy‐two total gastrectomies were performed. The Siewert‐Peiper gastric replacement procedure was used in 48 cases, while the Rou‐xen‐Y method was performed in 24 cases. Retrospective analysis showed no significant statistical difference between the 2 methods with regard to postoperative morbidity and mortality. There was an overall mortality rate of 11% and a morbidity rate of 45% (10% anastomosis breakdown, 27% pulmonary complications, 1% bowel obstruction, 7% other complications). As t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Our results revealed that the operative mortality with the extended total gastrectomy was not higher than with the proximal subtotal gastrectomy, and thus supported the resuits of Papachristou et al (1980). Although the operative mortality of total gastrectomy has been reported to be 10 to 20% (Hassler et al 1986), in our series it was only 1.9% with no differences in operative procedures and approaches. Therefore, extended total gastrectomy is considered to be a relatively safe operation and, in addition, enables us to perform curative resection for advanced cancers of the upper third of the stomach.…”
Section: Survivalsupporting
confidence: 81%
“…Our results revealed that the operative mortality with the extended total gastrectomy was not higher than with the proximal subtotal gastrectomy, and thus supported the resuits of Papachristou et al (1980). Although the operative mortality of total gastrectomy has been reported to be 10 to 20% (Hassler et al 1986), in our series it was only 1.9% with no differences in operative procedures and approaches. Therefore, extended total gastrectomy is considered to be a relatively safe operation and, in addition, enables us to perform curative resection for advanced cancers of the upper third of the stomach.…”
Section: Survivalsupporting
confidence: 81%
“…Although it is generally agreed that a total gastrectomy results in a higher surgical mortality than a distal subtotal gastrectomy, our present series in group B indicates no surgical deaths in the former procedure group when associated with splenectomy and caudal hemipancreatectomy (TSP: Table 2) but an overall 1.5% (2/137) surgical death rate in the total gastrectomy group (TSP + TS + T). In representative series, the surgical death rate in patients with total gastrectomy for gastric cancer regardless of curability ranges between 1.6% [7] and 11.1% [8] and, when restricted to the series dealing with the curative resection group, the surgical death rate ranges between 1.7% [5] and 42% [6].…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, as well as in many countries, the Roux-en-Y procedure seems to be the most preferred reconstruction [t] in order to avoid alkaline reflux esophagitis. There is a tendency for a decrease in the postoperative morbidity and mortality rates after total gastrectomy in recent years [2][3][4][5][6][7] (Table 2). No doubt the operation carries a certain frequency of late complications resulting in weight loss and Reprint requests: Lars Olbe, M.D., Associate Professor, Department of Surgery II, Sahlgren's Hospital, S-413 45 Gothenburg, Sweden.…”
mentioning
confidence: 99%